Research progress of diabetic osteoporosis: a comprehensive review - Ma, Xun; Zhang, Xiaoqian (Frontiers in Endocrinology, 2025)
Diabetic osteoporosis (DOP) is a complex metabolic bone disorder characterized by impaired bone quality and increased fracture risk in patients with diabetes mellitus. The interplay between hyperglycemia, insulin resistance, and bone metabolism underscores the need for integrated therapeutic strategies that address both glycemic control and bone health. This review systematically examines the molecular mechanisms of glucose-lowering and bone-protective agents, highlighting their dual roles in managing DOP. We discuss the pathophysiological pathways underlying DOP, including insulin/IGF-1 deficiency, advanced glycation end products (AGEs) accumulation, oxidative stress, and vascular damage. Furthermore, we explore the mechanisms of action of antidiabetic drugs (e.g., metformin, GLP - 1 receptor agonists, SGLT2 inhibitors) and anti-osteoporotic agents (e.g., bisphosphonates, teriparatide, strontium ranelate), emphasizing their potential synergies and risks. Finally, we outline future directions for developing novel therapeutics and optimizing combination therapies to achieve dual metabolic and skeletal benefits in DOP patients.